SUPPORTING LANGUAGE LEARNING FOR HEARING IMPAIRED STUDENTS THROUGH BLENDED LEARNING (Proceedings of International Conference on Special Education, 2015)
The struggles of hearing impaired students with reading, writing, and communication in mainstream classrooms have been well documented in the literature over the past two decades. With the proliferation of ubiquitous web-based technologies, there is a need to explore how technologies will help hearing impaired students in learning a second language. This study investigates the learning experiences of a group of hearing impaired students’ (N=14) learning the AK403 Communication in English 3 course conducted in a blended learning (BL) environment in a Polytechnic in Malaysia. Specifically, learning experiences were examined in the form of (1) the hearing impaired students’ perception towards the BL approach, and (2) the learning experiences supporting or impeding their learning using the BL approach. To gain an appreciation of the hearing impaired students’ experience with the BL system; both qualitative and quantitative techniques were used, namely a survey consisting of open and closed questions, and focus group interviews. Findings revealed the hearing impaired students’ have positive perceptions of the blended course. The BL platform afforded a few benefits but also posed a number of challenges for the students. Implications on how to better improve the blended learning environment were also discussed.